Commercialization of Underutilized Plants in Uganda: An analysis of the market chains of Luffa cylindrica L. - Barirega, Akankwasah; Van Damme, Patrick (Ethnobotany Research and Applications, 2014)
Luffa cylindrica L. (Cucurbitaceae) is an important plant with numerous domestic and industrial applications. In Uganda, mature fruits of this plant are sold in lots of markets as bathing sponges. The species has recently been identified as a priority plant for commercialization in Uganda. However, little is known about the structure and functioning of its value chain, demand and supply dynamics and economic viability of its trade. The objectives of this study were therefore to document and characterize luffa’s value chain, assess its demand and supply, and to evaluate economic viability of the plant’s trade in Uganda. Primary and secondary data were collected through a market survey and focus group discussions covering all the seven major markets in Kampala City. A total of 112 value chain actors were interviewed and two focus group discussions conducted with luffa traders. This study mapped and characterized the value chain of luffa in Uganda. The plant value chain was found to be fairly elaborate with farmers, primary processors, transporters, secondary processors, wholesalers, retailers and consumers recorded as major actors. Lack of market information, competition from alternative products and lack of awareness about alternative uses of luffa products were found to be the major bottlenecks in the luffa value chain. Despite luffa’s several domestic and industrial potential alternative uses, the study reveals that in Uganda, luffa is dominantly utilized as a bathing sponge. The supply of luffa to the market was found to be high as compared to the available demand. The luffa sponge traders were found to be economically benefiting from the trade with up to 30% net profit margins recorded in this study. While luffa is still underutilized looking at its potential values, commercialization of the plant is slowly emerging in Uganda.